Pengaruh Food Massage Terhadap Kualitas Tidur Pada Lansia Di Panti Wredha Dharma Bakti Kasih Surakarta - Dwi Ariani; Suryanti Suryanti (Poltekkes Kemenkes Surakarta, 2019)
Background: Sleep disorders the elderly in the Panti wredha Dharma Bhakti Kasih Surakarta can result in impaired immune function, decrease respiratory muscle capacity, disruption of the metabolic system, disruption of central nervous system regulation and psychological condition of patients impacting on long treatment period. Foot Massage is one of the complementary therapies that is considered safe and easy to administer and has the effect of improving circulation, removing the rest of the metabolism, increasing the range of motion of the joints, reducing the pain, relaxing muscles and providing comfort to the patient. The purpose of this study is to identify differences in the effect of sleep quality scores on control and treatment groups. Methods: This quasi-experimental study used a control group and a treatment group where each group performed a pretest and posttest assessment. The sample size was 40 patients. Sleep quality instrument used Richard Campbell Sleep Questionnaire (RCSQ). Data were analyzed by paired t-test and unpaired t-test. Results: The results showed that there was no significant difference in sleep quality. while in the treatment group, showed that there was a significant difference in sleep quality The difference in sleep quality score in the control group and treatment group was significant. Conclusion: Therefore, it can be concluded that sleep quality scores in the intervention group were higher than in the control group, thus foot massage is suggested to be used as evidence-based in hospitals as one of the complementary therapies that can be used as self-care interventions to help overcome patients with a critical sleep disorder.